2007
DOI: 10.1590/s0101-20612007000400005
|View full text |Cite
|
Sign up to set email alerts
|

Desidratação por imersão-impregnação de abacaxi em soluções de sacarose e em xarope de açúcar invertido

Abstract: ResumoEste trabalho foi realizado com o objetivo de avaliar a influência do tipo de soluto, da temperatura e concentração da solução hipertônica e do emprego de agitação da solução sobre a cinética de desidratação por imersão-impregnação de fatias de abacaxi. Os solutos utilizados foram a sacarose, em soluções com concentrações de 0,40, 0,44 e 0,47 g.mL -1 , e açúcar líquido invertido, sem diluição. Foram empregados: relação fruta -xarope de 1:10; dois níveis de temperatura da solução de desidratação, 40 e … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
8

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 18 publications
1
8
0
8
Order By: Relevance
“…This could be explained because once glycerol and sorbitol had low molar mass as compared to polydextrose and maltodextrin, more readily penetrate into the tissues of the root. These results were similar to those observed by Dionello et al (2007) who, studying the osmotic dehydration of pineapple in invert sugar and sucrose solutions, observed an increase of 3-4 times compared to the initial content of total soluble solids. According to Figures 2 and 3, the transport mechanism of water and solute occurred mainly during the first 2 h of immersion, followed by a period in which the mass transfer rate decreased gradually.…”
Section: Moisture Contentsupporting
confidence: 91%
See 2 more Smart Citations
“…This could be explained because once glycerol and sorbitol had low molar mass as compared to polydextrose and maltodextrin, more readily penetrate into the tissues of the root. These results were similar to those observed by Dionello et al (2007) who, studying the osmotic dehydration of pineapple in invert sugar and sucrose solutions, observed an increase of 3-4 times compared to the initial content of total soluble solids. According to Figures 2 and 3, the transport mechanism of water and solute occurred mainly during the first 2 h of immersion, followed by a period in which the mass transfer rate decreased gradually.…”
Section: Moisture Contentsupporting
confidence: 91%
“…Kotovicz et al (2013) investigated the effects of temperature, fructose concentration and edible coating on the kinetics of osmotic dehydration of yacon slices and found that at the beginning of the process, both the water removal rate and the difference between the water removal rate and the penetration rate of osmotic agent were high. Dionello et al (2007) observed that for different values of temperature in the OD processes with pineapple slices, the content of soluble solids increased significantly only in the first 30 min, remaining unchanged in the next 90 min of the process. This behavior demonstrated that solid gain due to the impregnation of the solute in the fruit surface layers was only significant in the first 30 min of the process.…”
Section: Moisture Contentmentioning
confidence: 93%
See 1 more Smart Citation
“…The following pretreatments were used for the enzymatic inactivation of the apple slices: a) Blanching by immersing the apple slices in water at 70°C for three minutes and cooling in a water bath at room temperature for five minutes (Haminiuk et al 2005); b) Acidification by immersing the apple slices in 1% (m/v) citric acid solution at room temperature for 15 minutes (Matusek et al, 2008). The fruit:solution ratio in the osmotic dehydration was 1:10 m/v (Dionello et al 2007, Elias et al 2008, Matusek et al 2008. After the process, the solution excess on the surface of the slices was removed with paper towel (Matusek et al, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…Os valores mencionados estão de acordo com os obtidos por PANADÉS et al (2006), que observaram que o ganho de sólidos na desidratação de pedaços de goiaba por 6 h em soluções de sacarose a 65 ºBrix variou no intervalo entre 2,3 ≤ δ ≤ 10,1, para temperaturas entre 30 e 50 ºC e grau de agitação de 100 min. Por outro lado, DIONELLO et al (2007) observaram efeito positivo significativo da concentração da solução de sacarose no ganho de sólidos durante a desidratação osmótica de fatias de abacaxi a 50 ºC, por 2 h a 60 min -1 . KARATHANOS et al (1995), na desidratação osmótica de maçãs em soluções de sacarose e glicose a 15; 30 e 45%, observaram que as amostras desidratadas em glicose apresentaram maior ganho de sólidos que aquelas desidratadas em sacarose.…”
Section: Ganho De Sólidosunclassified